Karakteristik Kewirausahaan Peternak Sapi Perah dan Korelasinya dengan Keberlanjutan Usaha Saat Outbreak PMK (Suatu Kasus di KPBS Pangalengan Kabupaten Bandung) - Markham, Marina Sulistyati; Firman, Achmad; Hermawan, Hermawan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The Foot and Mouth Disease (FMD) outbreak also impacted livestock farmers, causing livestock deaths, reduced milk production, and decreased livestock fertility. Farmers' incomes have fallen due to the end of livestock and reduced productivity and reproductive capacity. In this situation, livestock breeders must think and use entrepreneurial efforts, abandon old habits in traditional conservation management patterns that no longer make sense, and implement renewable innovations. Entrepreneurial characteristics and business sustainability are the most critical capital for surviving market competition in dairy cattle businesses. This research uses a questionnaire method. This research was conducted at TPK Warnasari, located in the KPBS working area of Bandung Regency. The approach used in this research is a mixed method (quantitative and qualitative approach). The sample was determined proportionally (proportional random sampling) from a population of 183 breeders in six groups, and then 75 respondents were selected. The analysis uses non-parametric rank-Spearman correlation analysis techniques. The results of the study show the characteristics of entrepreneurship in the middle category. Entrepreneurial characteristics support this, while business sustainability is in the medium category. The extensive skills and assets of farmers support this. There is a close relationship between entrepreneurship and the sustainability of dairy farmers in TPK Warnasari, with a coefficient of rank spearman= 0.735. This means that the higher the entrepreneurial value, the more sustainable the livestock business will be.